Commodities at a Glance: Special Issue on Cashew Nuts - United Nations Conference on Trade; Development (United Nations, 2021)
Cashew nuts enjoy increasing popularity all around the globe. The top three cashew-consuming countries – India, the United States of America and Germany - lie on three different continents. Cashews accounted for 17 per cent of world tree nut production in 2019/20, making it the third most popular tree nut after almonds and walnuts (INC 2020). Cashew nuts are consumed in a variety of forms including as salty or sweet snacks, ingredient of desserts and savory dishes, or further processed into cashew butter or ingredient of a variety of spreads, sauces, bars, and drinks. Rising demand for these products has led global cashew production to more than double between 2000 and 2018 (see Chapter 3). This report takes stock of the global cashew market and gives an overview of cashew production, trade patterns and policies. It also highlights opportunities for the cashew sector to foster value addition and diversification in cashew-growing countries, and its potential contribution to the Sustainable Development Goals (SDGs).